Pengaruh Media Audiovisual terhadap Prestasi Belajar Siswa dalam Mata Pelajaran Ipa Kelas VI SD Negeri Perdopo 02 Gunungwungkal - Dwi Husna Maulida; Nur Fajrie; Sri Surachmi W (Departement of Mathematics Education, 2023)
The purpose of this study was to find out descriptively the learning success of class VI students at SDN Perdopo 02 who studied with audiovisual media and did not learn with audiovisual media. Based on this comparison, the aim is to find out the science learning outcomes of class VI students at SDN Perdopo 02 in odd semesters between being taught with and without audio-visual media. The results showed that students in grade VI at SDN Perdopo 02 had a very high learning rate with an average of 23,500 audio-visual media and studied without audio-visual media. audiovisual media in the high category, an average of 18,500. The t-test gives tcount = 3.999 and p = 0.001 if p <0.01, so that comparing the results of the t-test it is concluded that a very significant value makes a difference in achievement in science learning from class VI SDN Perdopo 02 for students with audiovisual media and without audiovisual media.